PENGUATAN KARAKTER DAN PRESERVASI PENGETAHUAN MELALUI PEMBACAAN PRASASTI: STUDI PEMBACAAN PRASASTI DADIA ARYA DALEM TARUKAN - Ariyani, Luh Putu; Tantri, Ade Asih Susiari (ACARYA PUSTAKA, 2017)
The purpose of education in Hinduism is to establish an adult human or dewasa (dewasa= human with god character). Education is also an attempt to achieve Catur Purusa Arta (the four goals of human life). Having enough knowledge will help people build good characters. Strengthening the human characters are not only trained in the school but also in the family environment. Balinese tradition in transferring moral messages for the younger generation is very diverse. One of them is through the reading